INEL Nganasan Corpus - Brykina, Maria; Gusev, Valentin; Szeverényi, Sándor; Wagner-Nagy, Beáta (2025)
Corpus Citation Brykina, Maria; Gusev, Valentin; Szeverényi, Sándor; Wagner-Nagy, Beáta. INEL Nganasan Corpus. Version 1.0. Publication date 2025-05-02. https://hdl.handle.net/11022/0000-0007-FE63-C. Archived at Universität Hamburg. In: The INEL corpora of indigenous Northern Eurasian languages. https://hdl.handle.net/11022/0000-0007-F45A-1 Corpus Description The INEL Nganasan corpus has been created within the long-term INEL project ("Grammatical Descriptions, Corpora and Language Technology for Indigenous Northern Eurasian Languages"), 2016–2033. The corpus is largely based on the Nganasan Spoken Language Corpus, which has been adapted to the INEL standards and supplemented with new texts. The corpus makes possible typologically oriented corpus-based research on Nganasan and expands the documentation of the lesser described indigenous languages of Northern Eurasia. The INEL Nganasan corpus consists of two parts. The glossed (searchable) part of the corpus includes texts provided with source media files (whenever available) and annotated transcripts. The archival part of the corpus contains non-glossed texts, represented either by audio recordings (optionally – with preliminary transcriptions) or scanned pages of the manuscripts or publications. The corpus includes texts recorded between 1933–2019 in Nganasan. The sources of the corpus are: Audio recordings done by Maria Brykina, Valentin Gusev, Sándor Szeverényi and Beáta Wagner-Nagy. Legacy audio recordings done by A. Aksyonova, Svetlana S. Aksyonova, Josefina Budzisch, Michael Daniel, Oksana E. Dobzhanskaya, Eugene Helimski, Nadezhda T. Kosterkina, Jean-Luc Lambert, Marina D. Lyublinskaya, N. A. Popov, Florian Sobanski, Eugénie Stapert, Larisa Y. Turdagina, Zsuzsa Várnai, Peter Voliak, Tatjana Zhdanova and possibly other people. Legacy manuscript transcriptions done by Ekaterina P. Boldt, Eugene Helimski, Nadezhda T. Kosterkina, I. E. Machkinis, E. P. Nojfeld, A. K. Stolyarova, Natalia M. Tereshchenko and Tatjana Zhdanova. Texts published by Ekaterina P. ...